Integration of fluorescence differential path-length spectroscopy to photodynamic therapy of the head and neck tumors is useful in monitoring clinical outcome - Karakullukcu, Baris; Kanick, Stephen C.; Aans, Jan B.; Sterenborg, Henricus J. C. M.; Tan, I. Bing; Amelink, Arjen; Robinson, Dominic J. (Frontiers in Physics, 2015)
The use of fluorescence differential pathlength spectroscopy (FDPS) has the potential to provide real-time information on photosensitiser pharmacokinetics, vascular physiology and photosensitizer photobleaching based dosimetry of tumors in the oral cavity receiving m-tetrahydroxyphenylchlorin (mTHPC) photodynamic therapy (PDT). Reflectance spectra can be used provide quantitative values of oxygen saturation, blood volume fraction, blood vessel diameter, and to determine the local optical properties that can be used to correct raw fluorescence for tissue absorption. Patients and methods: Twenty-seven lesions in the oral cavity, either dysplasias or cancer were interrogated using FDPS, before and immediately after the therapeutic illumination. The average tumor center to normal mucosa ratio of fluorescence was 1.50 ± 0.66. mTHPC photobleaching was observed in 24 of the lesions treated. The average extent of photobleaching was 81% ± 17%. Information from FDPS spectroscopy coupled with the clinical results of the treatment identified 3 types of correctable errors in the application of mTHPC-PDT: Two patients exhibited very low concentrations of photosensitizer in tumour center, indicating an ineffective i.v. injection of photosensitiser or an erroneous systemic distribution of mTHPC. In one in tumor we observed no photobleaching accompanied by a high blood volume fraction in the illuminated tissue, suggesting that the presence of blood prevented therapeutic light reaching the target tissue. All 3 of the these lesions had no clinical response to PDT. In four patients we observed less than 50% photobleaching at the tumor margins , suggesting a possible geographic miss. One patient in this group had a recurrence within 2 months after PDT even though the initial response was good. The integration of FDPS to clinical PDT yields data on tissue physiology, photosensitiser content and photobleaching that can help identify treatment errors that can potentially be corrected.